The Spread of “Tradisi Mandi Uap” as a Track Identification of Spices in Indonesia - Gaya Mentari; Yuhaswita Yuhaswita (Indonesian Journal of Social Science Education (IJSSE), 2022)
The presence of spices in the archipelago became one of the pioneers for various cultural manifestations that appeared in various regions of the Indonesian archipelago. One form of the presence of spices that is reflected in this cultural form is the traditional steam bath tradition. The aims of the study were to 1) describe the distribution of bathing habits using spice water in several regions in the Indonesian archipelago. 2) mapping the distribution plots of spices in the archipelago through local traditions that have existed and are still alive in the community in certain areas of the archipelago; 3) showing the traditional steam bath tradition which has become a habit and has the potential to become an intangible cultural heritage in Indonesia. In conducting the study, it was used to search for sources of information from literature studies related to the spice bath tradition. The method used is a qualitative method by describing a map of the distribution of the spice bath tradition in the regions of the archipelago. The results of the study show that traditional steam bathing is a spice bath tradition that is spread across the eight regions in Indonesia and is dominated by people who have a background of Malay cultural influence. The eight areas include North Sumatra (Batak Karo), Jambi (Tanjung Bajo Village), Palembang, Pontianak (Mempawah), West Kalimantan (Sintang Regency), Sambas Regency, North Kayong Regency (Pangkalan Buton Village), and East Belitung.